The Psychological State of Lydia as A Child of Dysfunctional Family in Celeste NG’s “Everything I Never Told You” - Arinda Kairunnisa; Latifah Dwi Ariyani (Metaphor, 2020)
This study purposed in revealing : (1) the reflection of dysfunctional family in Celeste Ng’s “Everything I Never Told You” and (2) the psychological state of Lydia as the child of dysfunctional family in Celeste Ng’s “Everything I Never Told You”. Descriptive qualitative method is used to analyze the novel entitled “Everything I Never Told You” written by Celeste Ng as the object of research. The method of collecting data in this research includes reading, identifying, classifying, and selecting. The method of analysing the data are done by displaying, explaining, and interpreting. Dysfunctional family concept and Sigmund Freud’s psychoanalysis are used in analyzing the data. The finding shows that : (1) there are some reflections indicate the dysfunctional family in Celeste Ng’s “Everything I Never Told You”, such as, the cause of dysfunctional family shown by authoritarian parents, the characteristics of dysfunctional family shown by prolonged conflict and perfectionist expectation toward children, and the type of dysfunctional family in form of chronic conflict family; (2) the psychological state of Lydia as the child of dysfunctional family is illustrated by isolated and empty feeling, dependent due to fear of being abandoned, super responsibility by adopting the enabler type, feel guilty when looking for satisfaction for herself, and the ego defense mechanism in the form of regression. The psychological state of Lydia is described through the apparatus in her unconscious mind, there are, the id, the superego, and the ego.